An Operations management study on Tiger Machinery and Industrial Corporation - Batungbakal, Pia Marie S. (College of Engineering, 2004)
Tiger Machinery and Industrial Corporation (TMIC) is a manufacturer of metal replacement parts established in 1977. THe business is concerned with manufacturing and repairing spare parts, modifying existing designs to improve production, and trading imported products to companies in the power, cement, mining, quarrying and other allied industries. The company is divided into five divisions: (1) Machine Shop, (2) Fabrication, (3) Foundry , (4) Thermal Spray, and (5) Trading. The study will focus on the Foundry Division because it is the department that is currently experiencing problems in meeting customer deadlines. The foundry division casts manganese, stainless steels, cast irons, and other ferrous products. All products are manufactured on a made to order basis. TMIC's main concern is to meet the deadlines set by customers. After thorough documentation and analysis of the different aspects concerning the company's current operations management system, two problems were found to be major causes of unmet customer deadlines and other secondary problems. These are: (1) demand exceeding capacity and (2) lost production due to machine breakdowns. In order to address these problems, purchasing 7 additional finishing equipment is recommended. This was the found to be the least costly alternative (implementation cost = Php 38,500) that will be able to meet production requirements while maintaining the current workforce level and working hours. The implementation of a new scheduling system is also suggested. The new system will incorporate an allowance to the lead time quoted for regular orders. This allowance will be used for the production of sudden rush orders. This system assures that the production time for regular orders placed earlier will not be used for producing rush orders, and consequently, that the company will still be able to meet deadlines for regular products even while accepting rush orders.